Race, obesity, and the puzzle of gender specificity - Mary A. Burke; Frank Heiland (Federal Reserve Bank of Boston, 2008)
Obesity is significantly more prevalent among non-Hispanic African-American (henceforth black) women than among non]Hispanic white American (henceforth gwhiteh) women. These differences have persisted without much alteration since the early 1970s, despite substantial increases in the rates of obesity among both groups. Over the same time period, however, we observe little to no significant differences in the prevalence of obesity between black men and white men. Using data from the National Health and Nutrition Examination Surveys (NHANES) and the Behavioral Risk Factor Surveillance System (BRFSS) pertaining to the past two decades, we evaluate an extensive list of potential explanations for these patterns, including race and gender differences in economic incentives, in body size ideals, and in biological factors. We find that the gaps in mean BMI and in obesity prevalence between black women and white women do not narrow substantially after controlling for educational attainment, household income, occupation, location, and marital status-nor do such controls eliminate the gender-specificity of racial differences in obesity. Following these results, we narrow down the list of explanations to two in particular, both of which are based on the idea that black women (but not also black men) face weaker incentives than white women to avoid becoming obese; one explanation involves health-related incentives, the other, sociocultural incentives. While the data show qualified support for both explanations, we find that the sociocultural incentives hypothesis has the potential to reconcile a greater number of stylized facts.
Keywords: D11; I12; J15; Z13; 330; Körpergewicht; Ernährungsverhalten; Schwarze; Weiße; Frauen; USA